Implementation of the Project for Strengthening the Profile of Pancasila Students on Multicultural Insight at State Vocational High School: Implementasi Proyek Penguatan Profil Siswa Pancasila Berwawasan Multikultural di Sekolah Menengah Kejuruan Negeri - Hasriani, Hasriani; Alhabsyi, Firdiansyah; Mashuri, Saepudin; Akbar, Alfian; Mudaimin, Mudaimin; Nurmalasari, Nurmalasari (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2024)
This project's objective is to create students' character in line with the values ​​of Pancasila which have been inherited since the founding of Indonesia. This field survey using the case study method targets schools that have implemented a uniform independent learning curriculum across all classes Document analysis, observations, and interviews were used as data gathering methods.This research shows that the P5 project at SMKN 1 Palu has successfully promoted multicultural values such as tolerance, empathy, cooperation, and appreciation of diversity among students of different religions and cultures. Students can express their cultural identity and appreciate differences through various activities such as art exhibitions, work performances, and interactive learning in class. This research concludes that the P5 project can effectively strengthen multicultural values for the school environment includes students from various religions and cultures. This study suggests the need for continued support and collaboration between schools, families, communities, and the government to ensure the success of implementing P5 in schools. By synergizing with all stakeholders, we can encourage pupils should participate actively in efforts to maintain harmony of diversity and national resilience of the Indonesian nation.